2019
DOI: 10.1029/2019ms001894
|View full text |Cite
|
Sign up to set email alerts
|

Which Orographic Scales Matter Most for Medium‐Range Forecast Skill in the Northern Hemisphere Winter?

Abstract: It is generally accepted that increased horizontal resolution improves the representation of atmospheric circulation in global weather and climate models. Understanding which processes contribute toward this improvement can help to focus future model development efforts. In this study, a set of 10-day global weather forecasts, performed with different atmospheric and orographic resolutions ranging from 180 to 9 km, are used to examine the impacts of resolving increasingly smaller orographic scales on the forec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…The stratosphere is now well known to be important for medium‐range weather prediction, seasonal forecasting and climate projections (Butler et al., 2019), and orographic gravity waves play a significant role in its accurate representation (Alexander et al., 2010). Better resolved orography also leads to a better representation of the low‐level flow across mountains and valleys (Vannière et al., 2019) and, more generally, of the large‐scale circulation throughout the atmosphere (Kanehama et al., 2019).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The stratosphere is now well known to be important for medium‐range weather prediction, seasonal forecasting and climate projections (Butler et al., 2019), and orographic gravity waves play a significant role in its accurate representation (Alexander et al., 2010). Better resolved orography also leads to a better representation of the low‐level flow across mountains and valleys (Vannière et al., 2019) and, more generally, of the large‐scale circulation throughout the atmosphere (Kanehama et al., 2019).…”
Section: Motivationmentioning
confidence: 99%
“…The atmospheric circulation is much better represented in these high‐resolution simulations than with coarser grid spacing (tens to hundreds of km). Several studies have shown that the improvement in circulation, particularly over the Northern Hemisphere (NH) during winter, comes predominantly from the fact that the orography is better resolved (e.g., Berckmans et al., 2013; Kanehama et al., 2019). At these resolutions, important orographic effects become resolved, and there is a lesser need to parametrize them.…”
Section: Motivationmentioning
confidence: 99%
“…To more easily disentangle the impact of the resolved orography on the winter Northern Hemisphere circulation, both the TOFD and SSO schemes are turned off. This follows what was done in Kanehama et al (2019), in order to avoid interactions between resolved and unresolved orographic processes. As expected, turning off the two parametrizations leads to a considerable deterioration of the mean climate, causing an increase in the jet speed at both low and upper levels.…”
Section: Methodsmentioning
confidence: 91%
“…In this study, one of these aspects is explored: to what extent the increased fidelity of the higher horizontal resolution climate simulations is due to the fact that more orographic effects become explicitly resolved. Following Kanehama et al (2019), who explored this question for weather timescales, hereafter the term "atmospheric resolution' will be used to refer to the grid spacing at which the atmosphere and land surface are discretized. Similarly, the term "orographic resolution" will be used to 2 https://doi.org/10.5194/wcd-2021-51 Preprint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation